PENGEMBANGAN MEDIA BERBASIS VIDEO ANIMASI MENGGUNAKAN CANVA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS II SD NEGERI 117478 SIMATAHARI - Wita Triyani Dalimunthe; Umar Darwis (Bajang Institute, 2024)
This research aims to develop animated video-based media using Canva that is suitable for use in Indonesian language subjects in class II of SD Negeri 117478 Simatahari. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. In this research, researchers implemented the ADDIE development model only up to the Development stage. The instrument used to collect data was a questionnaire given to several expert validators, namely media expert validators, material expert validators and learning expert validators. The total score obtained from media expert validation is 86 in the